Exchange Rate Regime Considerations in an Oil Economy : The Case of the Islamic Republic of Iran - Celasun, Oya (IMF Working Papers; Working Paper ;, 2003)
This paper provides a brief overview of the evolution of exchange rate policy in the Islamic Republic of Iran from 1993 to 2002 and reviews the basic criteria for the choice of the exchange rate regime in the medium term. The analysis highlights the merits of an intermediate regime which would allow the authorities to smooth out excessive short-term exchange rate fluctuations while letting nominal exchange rate movements facilitate real exchange rate adjustments called for by major oil price shocks.